The Economics of Pollution Trading and Pricing under Regulatory Uncertainty - Knudsen, Odin K. (World Bank, Washington, DC, 2017)
In this paper, authors explore the effects of uncertainty on pricing of pollution permits, through the use of a dynamic model of pollution markets. Authors consider two major sources of uncertainty - that arising from the volatility of demand for the underlying resource and that coming from the regulatory environment. Both sources of uncertainty are common in pollution permit trading as not only does the market respond to the volatility of fundamentals but also to the vagaries of the institutional structure, created by public policy and enforced through regulation. The paper shows that even in the presence of strategic behavior on the part of the agents involved, the trading of permits effectively reduces emissions, and pricing does reflect opportunity costs and environmental objectives. Furthermore, and somewhat paradoxically, the higher uncertainty, the greater the impact of regulation.